Growth And Performance Of Manufacturing Sector of Punjab In Liberalization Era - Aggarwal, Rasleen (My University, 2010)
Liberalization, privatization and globalization are the buzzwords today. The government of India introduced major reforms in July 1991. After the advent of Liberalization, Privatization and Globalization (LPG) the manufacturing sector in Punjab is in the throes of a very significant phase of transition with severe challenges and many new opportunities. To compete in this globalized world, productivity of manufacturing sector is a crucial factor. The significance of productivity in increasing national welfare is now universally recognized. In every country, industry or organization, the main source of economic growth is a result of an increase inproductivity. Nowadays, it is widely accepted that productivity is a key performance benchmark for firm involved in the manufacturing sector. This is because improvement in productivity is related to increased profitability, lower costs and sustainable competitiveness. Productivity is defined as the efficient use of resources in the production of various goods and services. Rising productivity implies that either higher output is produced with the same amount of input, or that less input are required to produce the same level of output. The present comprehensive, in-depth study analyses the performance of Punjab manufacturing sector in terms of productivity. The present analyses the trends in productivity for the Punjab manufacturing for the period 1991-2007. To examine the impact of LPG on the manufacturing sector of Punjab, the entire period is dividing into two sub-periods. Period I is 1991 to 1999, and period II is 2000 -07 which is the post-2000 period. The study analyses the trends in output (value added), inputs (labour, capital), labour productivity, capital productivity and capital intensity for Punjab manufacturing sector at the disaggregate level for the entire period 1991-2007, as well as for sub-periods, period-I and period-II. An attempt has been made to trace the factors influencing total factor productivity for Punjab Manufacturing. A detailed analysis for pre-2000 and post- 2000 period shows that in terms of performance of labour productivity and capital productivity three industries, namely Tanning and dressing of leather #19 and publishing, printing and reproduction of recorded media #22 and coke, refined petroleum record a higher growth rate. The lower performance is recorded by motor vehicles #34, woods and products of wood #20, followed by electrical machinery
MP
Keywords: Performace; Manufacturing; Productivity